Analysis of Audience Reception of Dieting Lifestyle Posts Through Instagram Account @komunitasdietsehat - Gustin, Eliana Ardelia; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
This study aims to analyze the audience's acceptance of the dieting lifestyle displayed through the Instagram account posts @komunitasdietsehat. The reason researchers chose this topic is because the phenomenon of dieting is on the rise in Indonesia, where dieting has become a lifestyle for some people. The method used in this research is Qualitative. The informants in this study were 10 followers of the Instagram account @komunitasdietsehat. The data collection technique used in this research is indepth interview. The data analysis technique is based on the Miles and Huberman model. The results showed that the reception of the informants was positive. 6 informants entered into a hegemonic dominant position, informants agreed that the dieting lifestyle on @komunitasdietsehat Instagram account posts as motivation to lose weight and ideal. 4 informants entered into a negotiated code position, according to informants, the posts on the @komunitasdietsehat account are not only a motivation to lose weight, but the dieting lifestyle can also be done in other ways and according to their respective body portions.